The future of aid for education: Three essays. (April 2022) - Burnett, Nicholas; Lewin, Keith; Heyneman, Stephen
Abstract: There is a growing sense of disquiet that the UN Sustainable Development Goals on education are unrealizable in many of the poorest countries. The implications of this conclusion has been the subject of much discussion in this as well as other journals. We have tried to summarize our views by responding to four questions: (i) How should domestic revenues and other secure sources of recurrent finance be increased; (ii) what changes are needed in the international architecture of education and development; (iii) should educational assistance be concentrated on humanitarian emergencies, and (iv) should non-emergency educational assistance be concentrated on education public goods?